2020
DOI: 10.21518/2079-701x-2020-11-92-100
|View full text |Cite
|
Sign up to set email alerts
|

The use of the ultrasound for otorhinolaryngology, head and neck diseases (literature review)

Abstract: Despite the fact that otorhinolaryngologists are already very busy finding a solution to the problem of chronic tonsillitis, it remains unresolved. The prevalence of chronic tonsillitis does not decrease, but rather increases. Diseases of the tonsils are characteristic primarily of the child and adult working population. Chronic tonsillitis attracts attention not only as an independent disease, but as a cause of frequent local and especially systemic complications, which number more than 100. All these facts s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…studied the state of the palatine tonsils and lymph nodes in chronic tonsillitis by ultrasound, but only in adults. He differentiated the changes in various forms of the disease and found that patients with the allergic-toxic chronic tonsillitis had more pronounced changes in the tonsils, such as their irregular shape, unclear contours, the presence of additional inclusions, hypoechogenicity [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…studied the state of the palatine tonsils and lymph nodes in chronic tonsillitis by ultrasound, but only in adults. He differentiated the changes in various forms of the disease and found that patients with the allergic-toxic chronic tonsillitis had more pronounced changes in the tonsils, such as their irregular shape, unclear contours, the presence of additional inclusions, hypoechogenicity [13].…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of ultrasound examination are high informativeness, non-invasiveness, safety for children's body, painlessness; it can be used at any age. The use of ultrasound examination of the tonsils in children with chronic tonsillitis is a supplement to the visual examination and it allows to determine the condition of the tonsil tissues, the presence of cysts or scar changes [12,13].…”
Section: Introductionmentioning
confidence: 99%